Development Of Electronic Lkpd (E-Lkpd) Based On Problem Based Learning (Pbl) With Ethnoscience Content On Acid-Base Material Class Xi Mia At Smas Imelda Medan - El Kamty Yamareta Rahmawaty Sinaga; Marini Damanik (Universitas Lampung, 2025)
Development of Electronic LKPD (e-LKPD) Based on Problem Based Learning (PBL) with Ethnoscience Content on Acid-Base Materials Class XI MIA SMA SWASTA IMELDA MEDAN. This study aims to develop an Electronic Student Worksheet (e-LKPD) based on Problem Based Learning (PBL) with ethnoscience content on Acid Base material for class XI MIA students at SMA Swasta Imelda Medan. The research method used is Research and Development (R&D) with the ASSURE development model (Analyze Learner Characteristics, State Standards Objectives, Select Methods, Media and Materials, Utilize Media and Materials, Require Learner Participation, Evaluation). The research population was all class XI MIA 2 students of SMA Swasta Imelda Medan, with the same sample. The research data were analyzed using expert validity tests, student and practitioner (teacher) response questionnaires, and n-gain calculations. The results showed an increase in students' critical thinking skills in the experimental class by 78.29% (effective). The assessment of the developed media obtained a result of 92.44% (Very Interesting), and the average percentage of validator values ​​from material experts, media experts, and practitioner experts reached 94.17% (Very Valid). Thus, the PBL-based e-LKPD with ethnoscience content on the Acid Base material is effective and able to improve students' critical thinking skills.